Benefit to few versus risk to many: An ethical dilemma during coronavirus disease 2019 pandemic for deceased-donor organ transplant in a resource-limited developing country - Kute V.; Ramesh V.; Shroff S.; Prasad N.; Guleria S.; Prakash J.; Sahay M.; Modi P.; Cantarovich M.; Haberal M. (My University, 2025)
The tools in our armamentarium to prevent the transmission of coronavirus disease 2019, known as COVID-19, are social distancing; frequent handwashing; use of facial masks; preventing nonessential contacts/travel; nationwide lockdown; and testing, isolation, and contact tracing. However, the World Health Organization’s suggestions to isolate, test, treat, and trace contacts are difficult to implement in the resource-limited developing world. The points to weigh before performing deceased-donor organ transplant in developing countries are as follows: limitations in standard personal protective equipment (as approved by the World Health Organization), testing kits, asymptomatic infections, negative-pressure isolation rooms, intensive care unit beds, ventilator support, telehealth, availability of trained health care workers, hospital beds, the changing dynamic of this pandemic, the unwillingness of recipients, education updates, and additional burdens on the existing health care system. This pandemic has created ethical dilemmas on how to prioritize the use of our facilities, equipment, and supplies in the cash-strapped developing world. We believe that, at the present time, we should aim to resolve the COVID-19 pandemic that is affecting a large sector of the population by diverting efforts from deceased-donor organ transplant. Transplant units should conduct case-by-case evaluations when assessing the convenience of carrying out lifesaving deceased-donor organ transplant, appropriately balanced with the resources needed to address the current pandemic. © Başkent University 2021 Printed in Turkey. All Rights Reserved.